Akselerasi Daya Saing Produk Lokal Melalui Transformasi Visual Produk UMKM Menggunakan Teknologi AI - Mohammad Bayu Anggara; Wini Fetia Wardhani; Inka Aqila Nurfalqi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
Limited capability of Micro, Small, and Medium Enterprises (MSMEs) in producing appealing promotional visuals remains a major challenge in advancing local product competitiveness within the digital marketing environment. This issue is generally associated with inadequate visual design skills and restricted access to supporting technologies. This community service program aimed to improve the understanding and practical skills of MSME actors in Bandung Regency in the use of Artificial Intelligence (AI) technology as a supporting tool for creating promotional visual content. The program was conducted using a participatory approach through a seminar and workshop held on January 31, 2026, attended by 17 MSME participants. The learning methods combined lectures, group discussions, hands-on practice, and mentoring sessions. Program evaluation was carried out using pre-test and post-test instruments, accompanied by a participant satisfaction survey. The evaluation results indicated an increase in participants' understanding by 16.2%, rising from 78.7% in the pre-test to 94.9% in the post-test. Beyond cognitive improvement, the satisfaction survey results showed that most participants rated the program very positively, with average scores exceeding 4.5 on a 5-point Likert scale for material relevance, clarity of delivery, and overall program benefits. Participants were also able to produce tangible outputs in the form of AI-assisted promotional visuals, including product photographs, poster designs, and digital promotional content. These findings indicate that the application of AI technology in promotional visual training for MSMEs is effective in building business actors' capacities while achieving a high level of participant satisfaction